Metabolic Mechanism of Sulfadimethoxine Biodegradation by Chlorella sp. L38 and Phaeodactylum tricornutum MASCC-0025 - Li, Bing; Wu, Di; Li, Yan; Shi, Yan; Wang, Chenlin; Sun, Jiasi; Song, Chunfeng (Frontiers in Microbiology, 2022)
Antibiotic resistance is one of the most important environmental challenges. Microalgae has been considered as a promising green media for environmental purification. In this work, Sulfadimethoxine (SDM) biodegradation potential via Chlorella sp. L38 and Phaeodactylum tricornutum MASCC-0025 is investigated. Experimental results indicated that the tested freshwater and marine microalgae strains presented stress response to SDM addition. For Chlorella sp. L38, it has a good adaptability to SDM condition via antioxidant enzyme secretion (SOD, MDA and CAT up to 23.27 U/mg, 21.99 μmol/g and 0.31 nmol/min/mg) with removal rate around 88%. With increasing the salinity (adding a certain amount of NaCl) of cultivation media, SDM removal rate by Phaeodactylum tricornutum MASCC-0025 could achieve 100%. Although its adaptive process was slower than Chlorella sp. L38, the salinity advantage would facilitate enzyme accumulation. It indicated that microalgae could be used to remove SDM from freshwater and marine environment via suitable microalgae strain screening.